Peranan Orang Tua Siswa dalam Melaksanakan Pendampingan Pembelajaran dari Rumah Secara Online - Miftakhi, Diah Rina; Ardiansah, Feri (JOEAI (Journal of Education and Instruction), 2020)
The purpose of this research is to improve students' learning outcomes in science subjects grade VI SD Negeri 02 Ujan Mas by using lung respiratory media. This research uses a type of Class Action (PTK) research conducted in 2 cycles, each cycle consists of 4 stages, namely the stage of planning, implementation of actions, observation and reflection. This research subsection numbered 19 people. Data collection techniques are carried out through tests, and observations. Data analysis is done through observation data management. The results showed before learning using respiratory media (Pre-Test) learning results can be categorized as medium with a high category of 2 people, a moderate category of 15 people, and a low category of 2 people. Learning results when using respiratory media (Pre-Test) can be categorized as moderate or sufficient, this is evidenced by the results of learning in a high category of 0 people, a moderate category of 19 people and a low category of 0 people. The results of the analysis showed no significant influence of lung respiratory media on the results of science study grade VI SD N 02 this is evidenced by the results of rxy value data known correlation between variable X and variable Y of 0.061279 located at intervals of 0.00-0.20. In conclusion, the use of pulmonary respiratory media in grade 6 science lessons at SDN 02 Ujan Mas showed moderate or sufficient correlation in improving student learning outcomes, although statically it did not show significant influence. Keywords: Lung Respiratory Media, Learning Outcomes, Science Lessons